The Culture of Nurses in a Critical Care Unit - Scholtz, Suegnèt (Glob Qual Nurs Res, 2016)
Critical care nurses have to adapt to a fast-paced and stressful environment by functioning within their own culture. The objective of this study was to explore and describe the culture of critical care nurses with the purpose of facilitating recognition of wholeness in critical care nurses. The study had a qualitative, exploratory, descriptive, and contextual design. The ethnographic study included data triangulation of field notes written during 12 months of ethnographic observations, 13 interviews from registered nurses, and three completed diaries. Coding and analysis of data revealed patterns of behavior and interaction. The culture of critical care nurses was identified through patterns of patient adoption, armor display, despondency because of the demands to adjust, sibling-like teamwork, and non-support from management and medical doctors. An understanding of the complexity of these patterns of behavior and interaction within the critical care nursing culture is essential for transformation in the practice of critical care nursing.